Silicon Induces Salt Stress Amelioration in Sunflower Plants by Improving Photosynthetic Pigments and Mineral Status - Calero Hurtado, Alexander; Aparecida Chiconato, Denise; Sousa Junior, Gilmar da Silveira; Prado, Renato de Mello [UNESP]; Peña Calzada, Kolima; Olivera Viciedo, Dilier (MDPI, 2024)
Silicon (Si) has been extensively studied for its ability to decrease sodium (NaCl) toxicity in various plant species. Nonetheless, the processes that drive these responses are still not well understood. In this study, we investigate the effects of silicon (Si) on the modification of hydrogen peroxide concentration [H2O2], photosynthetic pigment content, nutrient accumulation, and the production of root and shoot dry biomass in sunflower (Helianthus annuus L.) plants hydroponically grown with NaCl (0 and 100 mM) in combination with Si (0 and 2.0 mM). Salt stress induced a significant decrease in plant growth due to high [H2O2] and a decrease in photosynthetic pigment content and nutritional status, denoting that there is oxidative and ionic stress. Nevertheless, Si addition to the growth medium consistently decreased the [H2O2] in sunflower and photosynthetic pigment content, and macro- and micronutrient accumulation, which was associated with an increase in root and shoot dry matter production. These findings indicate that adding Si to the growth medium is crucial for enhancing plant resistance to salt-induced ionic and osmotic stress, making it a promising strategy for improving crop growth and management under salinity conditions.
Keywords: Helianthus annus; ionic stress; osmotic stress; productivity; salinity; silicon